Pengaruh Price Discount Dan Fashion Involvement Terhadap Impluse Buying Pada Pengguna Tiktok Shop Kota Jakarta - Tamba, Rousdy Safari; Ningrum, Elin Kristia (JAMBIS : Jurnal Administrasi Bisnis, 2025)
This study aimed to find out the tendency of impulse buying among the people of the city of Jakarta and to find out whether there was an influence of impulsive buying on price discounts and fashion involvement. This research employed two independent variables, namely Price Discount (X1), Fashion Involvement (X2), and Impulse Buying as the dependent variable (Y). The formulation of the problem in this research included, among other things, finding out how Discount and Fashion Involvement influenced Impulse Buying and examining how TikTok users viewed impulse buying decisions made by Jakarta city residents. This research used quantitative methods. The data collection was carried out using a questionnaire distributed to 150 respondents in Jakarta. This questionnaire was given to Jakarta city residents who used the TikTok application. This research used data collection techniques, namely Incidental Sampling. The analysis was carried out by processing data using SPSS 26 for Windows. Then, the instrument was tested using validity and reliability testing and continued with classical assumption and hypothesis testing. This research found a significant and positive influence between online promotions (X1) and purchasing decisions (Y) of 0.441 or 44.1%. There was a substantial and positive influence between price perceptions (X2) and buying decisions (Y) of 0.323 or 32.3%. There was a significant and positive influence between online promotions (X1) and price perceptions (X2) on purchasing decisions(Y) of 0.439 or 43.9%